2011
DOI: 10.1155/2011/538637
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Thermomagnetic Convection in a Cavity Using the Lattice Boltzmann Model

Abstract: Thermomagnetic convection in a differentially heated square cavity with an infinitely long third dimension is numerically simulated using the single relaxation time lattice Boltzmann method (LBM). This problem is of considerable interest when dealing with cooling of microelectronic devices, in situations where natural convection does not meet the cooling requirements, and forced convection is not viable due to the difficulties associated with pumping a ferrofluid. Therefore, circulation is achieved by imposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Table 2 Thermomagnetic convection in a differentially heated square cavity with an infinitely long third dimension is numerically simulated using the single relaxation time lattice Boltzmann method (LBM) [52]. A dipole was located at the bottom of the enclosure to create a magnetic field, which circulate ferrofluids.…”
Section: Thermo-magnetic Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 Thermomagnetic convection in a differentially heated square cavity with an infinitely long third dimension is numerically simulated using the single relaxation time lattice Boltzmann method (LBM) [52]. A dipole was located at the bottom of the enclosure to create a magnetic field, which circulate ferrofluids.…”
Section: Thermo-magnetic Convectionmentioning
confidence: 99%
“…Hadavand & Sousa [52] Experimental study on thermomagnetic convection inside cavities. They examine the flow induced by convective currents inside a cavity with aspect ratio near the unity and the heat transfer rates measurements.…”
Section: Gontijo and Cunha [53]mentioning
confidence: 99%
“…Study of magnetohydrodynamic (MHD) flows, has been the subject of large number of numerical investigations [1][2][3]. Moreover, flows under external magnetic field are of practical interest such as crystal growth in liquids, cooling of nuclear reactors, electronic packages, micro electronic devices; and have been the subject of many earlier and recent studies for free fluid flows [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical and experimental studies have shown the effect of both large and small magnetic fields and temperature differences [12][13][14]. Hadavand…”
Section: Strength Of the Magnetic Field And Temperature Differencementioning
confidence: 99%
“…analytically showed that thermomagnetic convection will dominate over natural convection in a convective cell[12]. His set up included a square cavity with 2 mm long walls, with the top and the bottom wall adiabatic, the left and right wall were held at a constant temperature.…”
mentioning
confidence: 99%